TRAINING HIGH SCHOOL STUDENTS TO THINK CREATIVELY THROUGH VLOG LEARNING TOOLS BASED ON LOCAL WISDOM IN KAMPUNG SEMANGGI ORIENTED TOWARDS PROJECT-BASED LEARNING - Bunga Tiara Yulas; Tarzan Purnomo; Yuni Sri Rahayu (Universitas Labuhanbatu, 2026)
Purpose - This study aims to develop a valid, practical, and effective Vlog-based learning tool, integrated with the local wisdom of Kampung Semanggi Surabaya, to train high school students' creative thinking skills in ecosystem materials.Methodology - This research is a development study using the ADDIE model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The tools developed include teaching modules, student worksheets, Vlog media, and pretest-posttest instruments. The research subjects consisted of three expert validators, field observers, and 10th-grade high school students in the trial stage. Data were collected through validation sheets, observation sheets, and creative thinking skills tests. Data analysis was performed using percentages for validity and practicality and N-Gain calculations for effectiveness.Findings - The results showed that the teaching modules, Vlog media, LKPD, and test instruments achieved 93.50%, 88.50%, 89.00%, and 88.25%, respectively, all in the highly valid category. The results of the practicality test, based on the implementation of learning, showed an average implementation of 97.7% and a highly practical rating. The effectiveness test results showed an increase in students' creative thinking skills, as indicated by pretest-posttest scores, with an N-Gain value in the moderate range.Contribution - This study contributes to the development of a local wisdom-based biology learning tool that integrates digital media and the PjBL model, which has been proven effective in training students' creative thinking skills.